Safeguards and the problem of VERs - Phedon Nicolaides (Intereconomics, 1990)
One of the most complex problems facing GATT during the current Uruguay round of trade talks is the reform of Article XIX on temporary protection measures, commonly known as safeguards. Our author argues that, provided there are well-defined rules to limit its use, the introduction of some selectivity in safeguard measures need not undermine the GATT system. An appropriate change in the rules would induce countries to resort less to “grey-area” measures, such as voluntary export restraints.
Keywords: 330; Gatt